Radioimmuntherapie - Hecht, Markus; Gaipl, Udo; Fietkau, Rainer (Onkologe, 2021)
Background: Radiotherapy is used to achieve local tumor control in the irradiated area. In the last decade, there has been increasing evidence that radiotherapy has immunomodulatory properties in addition to killing tumor cells. Purpose: Essential principles of the immunomodulatory effects of radiotherapy are explained and, in particular, the clinical benefits of radiotherapy in combination with immune checkpoint inhibitors are presented. Results: Radiotherapy can trigger tumor-specific immune responses by inducing immunogenic cell death of tumor cells and alterations of the tumor microenvironment. However, clinical relevance of such systemic immunologic effects of local irradiation has been observed only very rarely in the past, which is probably due to the fact that irradiation can also induce immunosuppressive effects. By combining local radiotherapy with immune checkpoint inhibitors, antitumor immune responses can be enhanced and immunosuppressive effects can be counteracted. Such therapeutic strategies are currently being investigated in numerous clinical trials and have achieved remarkable results in non-small cell lung cancer (stage III) with the PD-L1 inhibitor durvalumab after definitive radiochemotherapy. Conclusion: The combination of radiotherapy with immune checkpoint inhibitors is an efficient concept that is currently being investigated in numerous studies and has already entered clinical routine in non-small cell lung cancer.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Immune checkpoint inhibitors; Immunogenic cell death; Immunotherapy; PD‑1; Radiotherapy